Influence of Different Treatment Protocols on Blood Biochemical Profile and Fertility in Crossbred Cows with Cystic Ovarian Degeneration - Chauhan, JH; Hadiya, KK; Dhami, AJ; Madhira, SP (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
The present study was conducted under field conditions on >90 days postpartum HF crossbred cows with cystic ovaries (n=58). The diagnosis was confirmed by history and trans-rectal palpation and ultrasonographic examinations twice at weekly interval using linear array transducer with 5.0-7.5 MHz frequency. The animals with follicular cysts were randomly treated either with conventional Ovsynch or with Ovsynch + CIDR protocol (n=10 each), and those having luteal cysts were treated either with Double PG injections 11 days apart or with modified Ovsynch protocol (n=16 each) with fixed time AI. A group of six cows having ovarian cyst was kept as untreated Control. Estrus response and conception rates at induced estrus/ fixed time AI were recorded. Blood samples were collected simultaneous to hormonal treatments on four occasions, i.e., on day 0 (day of first treatment), on day 7/11/14 (day of last PGF2α inj.), on day of induced estrus/FTAI, and on day 12 post-AI. The estrus induction response noted within 48 to 96 hrs of last PG injection among cystic cows treated with Ovsynch, Ovsynch + CIDR, Modified Ovsynch and Double PG protocols was 90.00, 100.00, 87.50 and 81.25 %, respectively. The conception rates at induced estrus with FTAI in cows under these protocols were 50.00, 40.00, 50.00 and 43.75 %, respectively. The variations in blood glucose, plasma cortisol, total protein and creatinine concentrations between periods of treatment were, however, statistically non-significant in cows under all four protocols, except creatinine in Ovsynch protocol. Furthermore, the effect of treatment/ period was also statistically non-significant among conceived and non-conceived cows in all four treatment protocols, except blood glucose which was significantly higher in non-conceived cows.